До питання про початковий період історії Новгорода-Сіверського - Кедун, І.С.; Черненко, О.Є. (Археологія і давня історія України, 2013)
Авторами статті розглядається історія вивчення вітчизняними дослідниками початкового періоду Новгорода-Сіверського. Проводиться співставлення даних писемних джерел та висновків істориків. Аналізується історична топографія центральної частини міста. Характеризуються археологічні комплекси, виявлені під час розкопок, вводяться до наукового обігу нові матеріали. В статье рассматривается история изучения отечественными исследователями начального периода Новгорода-Северского. Проведено сопоставление данных письменных источников и выводов историков. Анализируется историческая топография центральной части города. Рассматриваются археологические комплексы, выявленные в ходе раскопок города. Вводится в научный оборот новый археологический материал, полученный в ходе археологических раскопок авторов статьи. The article deals with the history of the early period of N.-Siverskyi study in the national historiography. The comparison of data from written sources and conclusions of historians, analyzes of historical topography of the city center have been made. Based on this study, the author comes to the conclusion that in the romensky period N.-Siverskyi was not a significant center, and there were only some small villages on the territory of future posad. Their merging took place in the XI century after joining the Middle Podesenya the administrative system of the ancient Russian state, along with the development of settlement on Zamkova gora. In this detailed study of the remains urgent questions of internal chronological early complexes N.-Siverskyi. Continuation of archaeological research will provide a clear answer to Bol on the evolution of the city and its surroundings in the initial period of their history. Remains urgent a detailed study of the early issues of the internal chronological complexes of N.-Ssverskyi. Continuation of archaeological research will provide a clear information on the evolution of the city and its surroundings in the early period of their history.